Caracterização do efluente gerado por abatedouro bovino e suíno e proposta para o seu tratamento - Martins, Andrew Magri (2020)
Effluents generated by cattle and pig slaughterhouse are characterized by high organic load and, without proper treatment, can lead to environment impacts such as eutrophication of water bodies, contamination by pathogenic organisms and microorganisms and contamination of groundwater. This work aimed characterize the effluent generated and propose a treatment system for a slaughterhouse that is located in the central-north region of Paraná. The method involved site visits to survey the industrial processes and the treatment system itself, physical-chemical analysis of the effluents generated and dimensioning of a new treatment system, seeking to make compatible with the existing one. The result was the proposition of a system with predominance of stabilization ponds with: fat box, anaerobic pond, two facultative ponds, maturation pond and infiltration pond. According to the dimensioning, the overall efficiency of the treatment system of BOD5 can reach 98,62%, meeting the parameters of CEMA resolution n° 070/09, establishing a launch standard of 60 mg/l. The hydraulic detention time found was 69,05 days. And the ponds can occupy a space of 0,27 ha, while the permeable area suitable for the excavations of new ponds has 0,9 ha, proving compatible.